EXPLORING THE INFLUENCE FACTORS IN CONSUMER PREFERENCES TOWARDS CAFE SELECTION: AN EMPIRICAL STUDY - Maritsha, Kamila; Kusuma, Lalu Tri Wijaya Nata; Dania, Wike Agustin Prima; Andriani, Debrina Puspita (JEMIS (Journal of Engineering & Management in Industrial System), 2025)
This study aims to identify the key factors influencing consumer purchasing decisions in the café industry in Malang City, Indonesia. With the rapid growth of café businesses in the region, understanding the preferences and behavioral patterns of café consumers has become crucial for developing effective marketing strategies. This research combines K-Means clustering and Structural Equation Modeling (SEM) to explore the influence of four main variables: marketing mix, café atmosphere, service quality, and electronic word of mouth (E-WoM). The study began by segmenting consumers based on their monthly income and café expenditure, resulting in four distinct clusters: low income–low expenditure, high income–high expenditure, high income–low expenditure, and moderate income–moderate expenditure. Validity and reliability tests confirmed the consistency and accuracy of the measurement instruments, with all indicators passing Confirmatory Factor Analysis (CFA) criteria, and most meeting the threshold for convergent validity through Exploratory Factor Analysis (EFA). The SEM analysis revealed that each segment responded differently to the influencing factors: service quality was significant for Cluster 1, while Cluster 2 was influenced by marketing mix, service quality, and E-WoM. Cluster 3 showed no significant influence from any variables, and Cluster 4 was mainly influenced by E-WoM. These findings suggest the need for segment-specific marketing and service strategies, such as enhancing interpersonal service for lower-income consumers and improving digital engagement for mid-range market segments.